2004
DOI: 10.1073/pnas.0405968101
|View full text |Cite
|
Sign up to set email alerts
|

Cryptochromes and neuronal-activity markers colocalize in the retina of migratory birds during magnetic orientation

Abstract: Migratory birds can use a magnetic compass for orientation during their migratory journeys covering thousands of kilometers. But how do they sense the reference direction provided by the Earth's magnetic field? Behavioral evidence and theoretical considerations have suggested that radical-pair processes in differently oriented, light-sensitive molecules of the retina could enable migratory birds to perceive the magnetic field as visual patterns. The cryptochromes (CRYs) have been suggested as the most likely c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
311
5
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(332 citation statements)
references
References 44 publications
12
311
5
4
Order By: Relevance
“…Light and eyes are required for certain migratory behaviors, and CRY has been found in photoreceptor tissues of several organisms. In the migratory bird garden warbler (Sylvia borin), CRY expression was localized in a subset of retinal ganglion cells associated with magnetic orientation behavior (Mouritsen et al 2004). Other theories and potential magnetoreceptors exist; however, this is clearly a fertile field of research that will possibly include characterization of exciting new CRY functions as it develops.…”
Section: Role Of Cryptochrome In Magnetoreceptionmentioning
confidence: 99%
“…Light and eyes are required for certain migratory behaviors, and CRY has been found in photoreceptor tissues of several organisms. In the migratory bird garden warbler (Sylvia borin), CRY expression was localized in a subset of retinal ganglion cells associated with magnetic orientation behavior (Mouritsen et al 2004). Other theories and potential magnetoreceptors exist; however, this is clearly a fertile field of research that will possibly include characterization of exciting new CRY functions as it develops.…”
Section: Role Of Cryptochrome In Magnetoreceptionmentioning
confidence: 99%
“…In vertebrates having both (6-4) PHR and clock CRY proteins, (6-4) PHR does not disturb the circadian clock, and conversely clockwork CRYs do not appear to directly contribute to DNA repair (22,23). Clockwork CRYs from different species have also been implicated in diverse processes, including nonvisual photoreception, sun compass orientation, and time-place learning (24)(25)(26)(27)(28)(29)(30)(31)). Yet, delays in mechanistic characterization of clock CRYs, caused in part by technical difficulties in protein expression and thus structure determination, have hampered biological understanding.…”
mentioning
confidence: 99%
“…Consequently, we used a nonelectronic technique: behavioral molecular mapping based on quantification of the neuronal activity-dependent marker ZENK (19,20,(25)(26)(27)(28). The major advantages of a behavioral molecular mapping approach compared with an electrophysiological approach are that we could obtain, in a noninvasive manner, a record of neuronal activation in the brain from awake, unrestrained birds, and that the potential artifacts often associated with the combination of electrophysiology and magnetic field stimuli could be avoided.…”
mentioning
confidence: 99%
“…In recent years, mounting behavioral and anatomical evidence has been accumulating that birds, at least, might have two independent magnetic senses: (i) iron-mineral-based sensors located in the upper beak, which are innervated by the ophthalmic branch of the trigeminal nerve (V1) (8,9,(11)(12)(13)(14)(15)(16), and (ii) a light-dependent chemical sense which is embedded in parts of the visual system (7,9,(16)(17)(18)(19)(20)(21). However, considerable scientific skepticism remains regarding both of these proposed magnetic senses because, so far, in birds, the studies that have reported changes in neurophysiological activity in response to magnetic field changes differ in their conclusions, could not be independently confirmed, and are likely to have been subject to artifactual difficulties (22)(23)(24).…”
mentioning
confidence: 99%